Examining the access to benefits and quality sterilization services among Muslim women in India - Govind Singh (BMC, 2024)
Abstract Background This research article examines the efficiency with which the Indian family planning programme provides care to Muslim women who opt to undergo tubectomies from public health facilities in terms of access to benefits/compensation as well as quality of services. The research subsequently intends to suggest suitable policies of affirmative action if required. Methods The research uses data from the women's file from the latest round of the National Family Health Survey (NFHS-5, 2019-21). Adjusted odds ratios are used to examine the likelihood of Muslim women (i) receiving compensations offered for undergoing tubectomies in public health facilities by the government, (ii) receiving comprehensive information prior to their tubectomies and (iii) reporting a good quality of care during their procedures, in comparison with non-Muslim women. Results The findings from the research indicate that Muslim women in India have lower odds of receiving state sponsored compensations in comparison with non-Muslim women in India (AOR = 0.67; CI: 0.60-0.76). Consequently, a lesser proportion of Muslim women reported receiving compensations in comparison with non-Muslim women. The difference in the receipt of compensations was 18 percentage points between both cohorts. Critically, despite their challenges in obtaining compensations, the findings from this research also indicate how Muslim women in India have higher odds of receiving comprehensive family planning information prior to their operation in comparison with non-Muslim women (AOR = 1.15; CI: 1.02-1.29). Discussion Given the existing dearth of evidence in family planning literature on the issue, this research article calls for greater attention and investments in understanding the reproductive health vulnerabilities of Indian Muslims, especially in the context of increasing social hostilities towards the community in India. In this regard, to promote the equitable delivery of family planning services, the findings from this research highlight the urgent need for institutional reforms that facilitate an easier access to public benefits among Indian Muslims.